Optimization and optimal control - Pardalos, P. M. (Panos M.), 1954-; Tseveendorj, Ider; Ėnkhbat, R. (Rėnt͡sėngiĭn) (Series on computers and operations research, 2003)
This volume gives the latest advances in optimization and optimal control which are the main part of applied mathematics. It covers various topics of optimization, optimal control and operations research.